MENINGKATKAN KEMAMPUAN MEMBACA HURUF HIJAIYAH MELALUI MACROMEDIA FLASH PLAYER PADA ANAK TUNAGRAHITA RINGAN - Syarifah Hidayati; Amsyaruddin -; Asep Ahmad Sopandi (Universitas Negeri Padang, 2013)
Abstract: This research background by the problems that researchers find in SLB Muhammadyah Pauh IX Padang, a mild mental retardation children who have difficulty in reading skills hijaiyah letters. This can be seen when a child is learning in class religious subjects, having observed the boy had difficulty in reading letters hijaiyah with correct pronunciation while the child was sitting in class V. Based on this research it is intended that the children can read letters hijaiyah with the correct pronunciation, and see if the Macromedia Flash Player can improve the child's reading ability hijaiyah letter with the correct pronunciation.This research uses experimental research is in the form of Single Subject Research (SSR) with the AB design. Observations conducted two sessions, namely sessions and session intervention baseline, baseline sessions before the intervention is given seven times of observation, the percentage of literacy hijaiyah letter with the correct pronunciation of this condition lies in the range of 0%, 10%, 20%, and 30% . Second, the intervention sessions using the Macromedia Flash Player, observations were made as much as thirteen times, the percentage of literacy hijaiyah letter with the correct pronunciation of this condition lies in the range of 30%, 40%, 50%, 60%, 70%, 80%, and 100%. Based on these results it can be concluded that the Macromedia Flash player to improve reading skills for children hijaiyah letter grade mild mental retardation DV / C in SLB Muhammadyah Padang Pauh IX. Kata-kata kunci: kemampuan membaca huruf hijaiyah; Macromedia Flash Player; anak tunagrahita.